Significance and Biological Importance of Pyrimidine in the Microbial World. (23rd March 2014) - Sharma, Vinita; Chitranshi, Nitin; Agarwal, Ajay Kumar
Abstract : Microbes are unique creatures that adapt to varying lifestyles and environment resistance in extreme or adverse conditions. The genetic architecture of microbe may bear a significant signature not only in the sequences position, but also in the lifestyle to which it is adapted. It becomes a challenge for the society to find new chemical entities which can treat microbial infections. The present review aims to focus on account of important chemical moiety, that is, pyrimidine and its various derivatives as antimicrobial agents. In the current studies we represent more than 200 pyrimidines as antimicrobial agents with different mono-, di-, tri-, and tetrasubstituted classes along with in vitro antimicrobial activities of pyrimidines derivatives which can facilitate the development of more potent and effective antimicrobial agents.